Simulation of the Structure and Track of the Tropical Cyclone Sidr using Numerical Models - Akhter, M. A. E.; Alam, M. M.; Mallik, M. A. K. (Journal of Scientific Research, 2016)
Tropical cyclone (TC), one of the most devastating and deadly weather phenomena,is a result of organized intense convective activities over warm tropical oceans. In the recent years, mesoscale models are extensively used for simulation of genesis, intensification and movement of tropical cyclones. During 09-16 November, 2007, a severe cyclonic storm named, Sidr was active in the Bay of Bengal part of the Indian Ocean. At 16 UTC on 15 November 2007, the system crossed Bangladesh coast near at long. 89.8 °E. In the present study, two state-of-the-art mesoscale models, MM5 and WRF, have been used to simulate the structure and track of TC Sidr. Horizontal resolution of 90 km and 30 km respectively for mother and nested domain were used in both the models. Various meteorological fields viz. central pressure, winds, vorticity, temperature anomaly etc. obtained from the simulations are verified against those observed to test their performance. The simulated tracks are also compared with those obtained from JTWC. The results indicate that MM5 model has better forecast skill in terms of intensity prediction but WRF model has better forecast skill in terms of track prediction of the cyclonic storm.